Open Source Systems: Towards Robust Practices 13th IFIP WG 2.13 International Conference, OSS 2017, Buenos Aires, Argentina, May 22-23, 2017, Proceedings - Balaguer, Federico; Di Cosmo, Roberto; Garrido, Alejandra; Kon, Fabio; Robles, Gregorio; Zacchiroli, Stefano (IFIP Advances in Information and Communication Technology, 2017)
collaboration; information systems; Linux; open access; open source software